KEPENTINGAN NASIONAL AUSTRALIA DENGAN MENJADIKAN BALI SEBAGAI DESTINASI WISATA FAVORIT (2018) - Nathalia Monica Kristy; Setyasih Harini; Halifa Haqqi (Solidaritas, 2020)
Australia, which is Indonesia's closest neighbor, has more than just business, security and proven political relations with Australians who make Bali their favorite tourist destination. Although the relationship between Australia and Indonesia had experienced ups and downs, it did not make the relationship between the two countries hostile but became even closer to the efforts to resolve the problem. The existence of a Travel Warning issued by the Australian Government because of Indonesia's critical situation did not discourage Australians from visiting Bali, with various efforts made by the Government of Bali to give positive views to Australians. This is proven by the increase in visits every year and the